2020
DOI: 10.1136/jitc-2019-000491
|View full text |Cite
|
Sign up to set email alerts
|

Lung metastases share common immune features regardless of primary tumor origin

Abstract: BackgroundOnly certain disseminated cells are able to grow in secondary organs to create a metastatic tumor. Under the hypothesis that the immune microenvironment of the host tissue may play an important role in this process, we have categorized metastatic samples based on their immune features.MethodsGene expression data of metastatic samples (n=374) from four secondary sites (brain, bone, liver and lung) were used to characterize samples based on their immune and stromal infiltration using gene signatures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 43 publications
3
72
0
1
Order By: Relevance
“…Thus, the immune populations recruited in response to DTCs may greatly differ across organs. Interestingly, recent work showed that lung metastases have a higher immunogenic signature compared to metastases in bone, liver and brain [48]. Although a wide heterogeneity in metastatic immune environment, lung metastatic samples exhibited increased lymphocyte and DC infiltration consistent with the active local immune system in lungs [48].…”
Section: Influence Of Host Organ In the Immune Landscape Of Metastasesmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, the immune populations recruited in response to DTCs may greatly differ across organs. Interestingly, recent work showed that lung metastases have a higher immunogenic signature compared to metastases in bone, liver and brain [48]. Although a wide heterogeneity in metastatic immune environment, lung metastatic samples exhibited increased lymphocyte and DC infiltration consistent with the active local immune system in lungs [48].…”
Section: Influence Of Host Organ In the Immune Landscape Of Metastasesmentioning
confidence: 98%
“…Interestingly, recent work showed that lung metastases have a higher immunogenic signature compared to metastases in bone, liver and brain [ 48 ]. Although a wide heterogeneity in metastatic immune environment, lung metastatic samples exhibited increased lymphocyte and DC infiltration consistent with the active local immune system in lungs [ 48 ]. In addition, immunogenic profiles in liver and brain metastases appeared to be independent of the primary tumor origin.…”
Section: Immune Surveillance Of Disseminated Tumor Cells (Dtcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Gene Set Enrichment Analysis (GSEA) was further used to investigate the functional enrichment with R package "Pi" (23). To explore the correlation between the expression levels of FCER1G and immune status, a total of 25 immunity-related gene sets covering both innate and adaptive responses were from a previous study (24)(Supplementary materials). Gene Set Variation Analysis from R package GSVA (20) was performed to obtain the immune pro le of the glioma samples.…”
Section: Immune Cells and Bioinformatic Analysismentioning
confidence: 99%
“…To predict their putative response to anti-PDL1 drug, glioma samples were scored with the GSVA method using the T-cell in ammatory (TIS) signature. This signature was derived from a previous study (24) and listed in Supplementary Materials.…”
Section: Quantify Of Relative Abundance Of Tiics and Prediction Of The Immunotherapy Responsementioning
confidence: 99%